Prevalence and genotypic characteristics of anal papillomavirus infection in a cohort of HIV-positive men who have sex with men - Collins, Jaime A. (2024)
Objective:To determine the prevalence and genotypic characteristics of anal papillomaviruses in HIV-positive men who have sex with men (MSM). Materials and methods: This is a prospective cross-sectional observational study of HIV-positive MSM at Almenara General Hospital between September 2017 and December 2018. HPV detection and typing was performed using a polymerase chain reaction technique that evaluated 21 genotypes stratified according to oncogenic risk into six low-risk and fifteen high-risk. Results: we evaluated 214 HIV-positive MSM. The overall prevalence of anal infection by papillomavirus infection was 70% (150/214). 86% (129/150) were caused by high-risk genotypes, 79% (102/129) of them were affected by a two or more-papillomavirus genotype. The most frequent high-risk genotypes were HPV-16, 31% (46/150); HPV-52, 22% (33/150); HPV-33, 21% (31/150); HPV-58, 21% (31/150) and HPV-31, 20% (30/150). In addition, HPV-18 reached 7% (10/150). The most frequent low-risk genotypes were HPV-6, 30% (45/150) and HPV-11, 29% (44/150). Conclusions: Prevalence of anal papillomavirus infection in HIV-positive MSM is very high in the hospital investigated. Most of these infections occurs with high-risk oncogenic genotypes. Papillomavirus 16 was the most frequent high-risk genotype.